Prevalence of hepatitis B and C at a major tuberculosis centre in Denmark. Issue 3 (4th March 2021) - Jørgensen, Anja; Bjørn-Mortensen, Karen; Graff Jensen, Sidse; Sloth Andersen, Ellen; Ravn, Pernille
Abstract: Background: Denmark is a low-prevalence country for tuberculosis (TB), hepatitis B (HBV), and hepatitis C (HCV) but the three diseases have similar sociodemographic risk factors. We estimated the prevalence and possible risk factors of HBV and HCV among TB-patients in a large TB clinic in Denmark. Methods: All patients starting anti-TB-treatment at Copenhagen University Hospital, Herlev-Gentofte from April 1 st 2018 through June 1 st 2019 were included. Results from HBV and HCV testing as well as sociodemographic information were collected. Risk factor analyses were carried out using descriptive statistics. Results: Of 82 patients tested for HBV, one (1.2%) had chronic HBV and 16 (19.5%) had serocleared HBV. Of 91 patients tested for HCV, three (3.3%) had chronic HCV and one (1.1%) had serocleared HCV. Country of origin other than Denmark was significantly associated with HBV-seropositivity among TB-patients, particularly patients from Greenland, Asia, Africa and Eastern Europe. No other significantly associated risk factors were found. Conclusion: The prevalences of chronic and prior HBV and HCV among TB-patients were lower compared to studies in TB high endemic areas but higher than those found in the Danish background population. We calculated the number needed to test to find one patient with HBV ranged between 27 and 83 and we suggest continuing screening of chronic HBV and HCV in TB-patients in Denmark.